Some Considerations on the Funnels from Tell Afis - Minunno, Giuseppe (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
Among the evidence yielded by the excavations carried out by the Italian Archaeological Mission at Tell Afis (in North-Western Syria, at the Northern border of the Idlib Plain), since 1986 directed by Stefania Mazzoni (University of Florence), many interesting features come from the acropolis, where remains of ritual spaces and activities dating from the Iron Age could be identified. In area A, where sacred buildings had been built since at least Iron Age I, the imposing remains of an Iron Age III temple (Temple AI) have been recovered (Mazzoni 2010a; 2010b; 2011; 2012: 30-32). Mostly in connection to this building a peculiar kind of pottery ‘funnels’ was found. This note concerns their function and interpretation.